Pengaruh Ukuran Perusahaan, Growth dan Media Exposure Terhadap Pengungkapan Corporate Social Responsibility - Nur Sadiah Hasibuan; Fitrisia Fitrisia; Mulyaning Wulan (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
This research purposes to determine the effect of firm size, growth and media exposure for Corporate Social Responsibility Disclosure. This research uses food and beverage subsector manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2014-2018. The total number of companies used as as sample is 8 companies The result of simultant test, firm size, growth and media exposure has an impact on Corporate Social Responsibility Disclosure. While the result of t test showed a significant positive effect of variable firm size and media exposure on CSR Disclosure. While variable growth showed not significantly effect positive on CSR Disclosure.